Traditional homemade Tunisian vinegars: Phytochemical profile, biological, physicochemical and microbiological properties. (December 2021) - Ben Hammouda, Mouna; Mahfoudhi, Amira; Gharsallah, Houda; El Hatmi, Halima; Attia, Hamadi; Azabou, Samia
Abstract: Grape (GV), fig (FV), prickly pear (PPV) and date (DV) vinegars are the most popular Tunisian homemade vinegars. Throughout the present study, we investigated the diversity of these fruit vinegars in terms of their physicochemical, microbiological and biological properties, as well as their phytochemical profiles. Despite a great variability between their characteristics, all vinegar samples showed significant total phenolic and flavonoid contents which ranged from 286.36 to 1636.75 mg GAE/L and from 240.58 to 755.84 mg QE/L, respectively. Through the evaluation of their antioxidant activity via DPPH, iron reducing antioxidant power (FRAP) and metal chelating assays, all vinegar samples showed important antioxidant potential which could be associated with their richness in phytochemical compounds. Indeed, 19 phytochemicals were identified using LC-MS, with the most abundant being quinic, protocatchuic, p- coumaric, and transferulic acids. Antimicrobial activity of vinegars was tested against Gram-positive and Gram-negative bacterial strains as well as against fungal strains. Results revealed that most of vinegar samples were found to be more inhibitive against bacterial strains than against fungal ones. Overall, these results indicated the high potential of Tunisia homemade fruit vinegars as antioxidant and antimicrobial agents that could be used as functional food ingredients. Highlights: Grape, fig, prickly pear and date vinegars are the famous Tunisian homemade vinegars. The chemical characteristics reveals a great variability between vinegar samples. Tunisian homemade vinegars have rich bioactive compounds mainly quinic and protocatchuic acids. Important antimicrobial and antioxidant potential of traditional Tunisian vinegars.